Language, Ethnicity, and Belonging for the Children of Migrants in New Zealand. (June 2018) - Cunningham, Una; King, Jeanette
The children of migrants grow up with influence from at least two cultures, and they must negotiate their path to adulthood through one or more ethnicities and one or more language varieties that may set them apart from the majority population. We asked how teenagers born to migrant parents in an English-speaking context appeal to the cultures and/or ethnicities they identify with to explain their language choices and perceptions of belonging. More than 50 interviews were carried out with teenagers who identified as speakers of the minority language of their parents (Chinese, Dutch, French, German, Korean, or Spanish), and one or both parents of such young people. The focus of the interviews was the minority language, but they became narratives of belonging. Thematic analysis of the transcribed and (where necessary) translated interviews revealed patterns in the perceptions of the teens and their parents. The reported self-perceived proficiency of the teenagers in the minority language, their perception of their ethnicity (particularly but not exclusively for the Chinese and Korean teens) and the culture of the host country, diasporic, and home country communities- were factors in when and how the teens chose to use the minority language, and in how they identified as, for example, Dutch. More than 160 languages are spoken in New Zealand; 25% of the population was born elsewhere, yet the country is one of the most monolingual in the world. This study reveals tensions affecting the willingness of New Zealand–born young people to openly identify with their parents' ethnicity and to use their languages. Lessons learned from those who raised bilingual children in New Zealand in the face of minimal official support and overwhelming pressure from English will be valuable to other parents and caregivers in New Zealand and elsewhere.